5+6(x+9)=59-9(3x+11)

Simple and best practice solution for 5+6(x+9)=59-9(3x+11) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5+6(x+9)=59-9(3x+11) equation:



5+6(x+9)=59-9(3x+11)
We move all terms to the left:
5+6(x+9)-(59-9(3x+11))=0
We multiply parentheses
6x-(59-9(3x+11))+54+5=0
We calculate terms in parentheses: -(59-9(3x+11)), so:
59-9(3x+11)
determiningTheFunctionDomain -9(3x+11)+59
We multiply parentheses
-27x-99+59
We add all the numbers together, and all the variables
-27x-40
Back to the equation:
-(-27x-40)
We add all the numbers together, and all the variables
6x-(-27x-40)+59=0
We get rid of parentheses
6x+27x+40+59=0
We add all the numbers together, and all the variables
33x+99=0
We move all terms containing x to the left, all other terms to the right
33x=-99
x=-99/33
x=-3

See similar equations:

| −7x+4=23 | | -15x+13=5 | | -20=8x-4x²-3 | | 9=2y+9= | | 4(x^2+15x)=216 | | −15x+13=5 | | 7t=18=-166 | | 2(x+5)(x−1)=0 | | -22=3s-(-8)= | | 9x+25+3x-1=180 | | -9x+7=12 | | −9x+7=12 | | 2(5x+3)=10x-3x+2 | | 4(y+8=22 | | 5x-8+11x+10=180 | | Y=20.2-0.8x | | (k-7)/16=-1 | | 5-8|-2x|=-75 | | 68=(-10b)+8 | | Y=0.8x+20.2 | | y=6.8+60 | | x+4x+7x-10+10x=180 | | 7x-4=4x-10 | | −18x+5=47 | | (n+1)=90 | | 2z=–8.8 | | -2y=48-3y= | | −8x+3=22 | | 35x+500=1,200 | | 1.2f=36 | | 3x-19=29-x | | 3x-19=29-× |

Equations solver categories